Indonesian Sentence Patterns of Five-Year-Old Children at Dharma Wanita Maperaha Kindergarten, Sawerigadi District, West Muna Regency: Pola Kalimat Bahasa Indonesia Anak Usia 5 Tahun di TK Dharma Wanita Maperaha Kecamatan Sawerigadi Kabupaten Muna Barat - Sarmel; La Yani Konisi; Rachman (PT. CASA CENDEKIA MEDIA, 2026)
The ability to construct sentences is a key indicator of syntactic development in early childhood language acquisition, particularly in bilingual environments where children negotiate the use of a local language and Indonesian. This study aims to describe the Indonesian sentence patterns produced by five-year-old children at Dharma Wanita Maperaha Kindergarten (TK Dharma Wanita Maperaha), Sawerigadi District (Kecamatan Sawerigadi), West Muna Regency (Kabupaten Muna Barat). This research employed a qualitative descriptive field design. The data consisted of children's oral utterances obtained from nine five-year-old children through observation, note-taking, and audio recording. The data were transcribed, reduced, classified, and analyzed using syntactic function analysis based on the categories of subject and predicate in Indonesian grammar. The findings show three major patterns: Subject (S), Predicate (P), and Subject-Predicate (S-P). Predicate-centered utterances were the most dominant, indicating that children tend to prioritize actions, commands, prohibitions, or communicative intentions while omitting explicit subjects. Subject-only utterances appeared as nominal or pronominal fragments, whereas S-P utterances showed the emergence of minimal complete clauses. The study concludes that the syntactic development of five-year-old children in this context is still dominated by elliptical and context-dependent structures, but it has moved toward the formation of more complete clauses. The scientific contribution of this study lies in proposing a three-layer mapping of early Indonesian syntax in a bilingual kindergarten context: nominal topic fragments, predicate-centered elliptical utterances, and emerging minimal clauses.